Characterization of a cloned histone gene cluster of the newt Notophthalamus viridescens. - Stephenson, E C (1981)
We report the cloning and characterization of a histone gene cluster of the newt Notophthalamus viridescens. Fragments containing newt histone genes were identified in whole genome Southern blots; these fragments were cloned into a bacteriophage lambda cloning vector constructed for this purpose. The positions of most of the histone genes were determined by hybridizing subcloned sea urchin histone genes to digests of the cloned newt gene cluster. The position of each gene was verified, and its polarity determined by sequencing a portion of each. The order of the genes in the cloned segment is H1-H3-H2B-H2A-H4, with each of the genes but H2B being transcribed in the same direction. Subcloned segments of the histone gene repeat were used to determine the size of each newt oocyte histone mRNA.